Comparing the Use of Uterine Artery Embolization to Gonadotropin-Releasing Hormone Agonists in Shrinking Fibroid Size: A Pilot Study in Kazakhstan - Balkenzhe Imankulova; Alibek Mereke; Nazira Kamzaeva; Talshyn Ukybassova (University Library System, University of Pittsburgh, 2015)
Introduction: Uterine fibroids are the most common benign tumor in women in Kazakhstan. In the past two decades, endoscopic surgery has played an important role in the development of gynecologic surgery, particularly in the treatment of uterine fibroids. The goal of this paper is to evaluate whether uterine artery embolization (UAE) or gonadotropin-releasing hormone agonists (GnRHa) prior to myomectomy was more effective in decreasing fibroid size and improving surgical outcomes in a pilot study of women in Kazakhstan. Methods: This pilot investigation included 24 patients separated into 2 groups: medication group (pre-treatment with GnRHa - 13 patients) and embolization group (pre-treatment with UAE - 11 patients). All patients had uterine fibroids, 3-10 cm in diameter, and were treated with myomectomy at the National Research Center for Maternal and Child Health, Astana, Kazakhstan. All patient data were obtained by a retrospective medical records review. Descriptive statistics were utilized to characterize participant demographics data. Independent t-tests were used to analyze continuous variables, and Chi-square and Fisher's exact tests were used where appropriate for count data. Results: The group treated with GnRHa had an operating time of 40±10 minutes longer than the group treated with UAE, due to the peri-operative difficulties encountered by surgeons in detecting the layer between the myometrium and fibroid capsule. The group treated with UAE experienced better patient outcomes (less blood loss, less surgical time, and reduced use of anesthesia) and was a technically easier surgery due to visible differences in uterine layers. Conclusions: Despite the fact that both treatments (GnRHa and UAE) were effective for fibroid shrinking, embolization resulted in more optimal surgical time and improved patient outcomes. Results of this pilot study need to be confirmed in a randomized clinical trial, specifically focused on Kazakhstan and the Central Asian Region.